Bortezomib retreatment for relapsed and refractory multiple myeloma in real‐world clinical practice. Issue 1 (7th December 2018) - Hulin, Cyrille; de la Rubia, Javier; Dimopoulos, Meletios A.; Terpos, Evangelos; Katodritou, Eirini; Hungria, Vania; De Samblanx, Hadewijch; Stoppa, Anne‐Marie; Aagesen, Jesper; Sargin, Deniz; Sioni, Anastasia; Belch, Andrew; et al.
Abstract: Aims: Studies have shown that bortezomib retreatment is effective in relapsed/refractory multiple myeloma (MM). The observational, prospective electronic VELCADE ® OBservational Study (eVOBS) study assessed bortezomib‐based therapies for patients with MM in everyday practice. Here, we report on those patients receiving retreatment with bortezomib. Methods: Consenting adults scheduled to receive bortezomib for MM were enrolled at 162 sites across Europe, Canada, Brazil, Russia, and Turkey between 2006 and 2010. Retrospective data on prior therapies and prospective observational data after bortezomib initiation were captured electronically at baseline, after every bortezomib cycle, and every 12 weeks after discontinuation or progression. Investigator‐assessed responses and adverse events (AEs) were evaluated. Results: Ninety‐six of 873 patients enrolled to eVOBS received bortezomib as first retreatment for progressive disease during the prospective observation period. Median age was 62 years, 53% were male, and median number of prior therapies at retreatment was 4. Overall, 41% of patients initiated bortezomib retreatment in combination with dexamethasone, 16% in combination with lenalidomide, and 21% received monotherapy. Rate of partial response or better (≥PR) was 75% at initial bortezomib therapy, including 44% complete response (CR)/near CR (nCR); at retreatment, ≥PR rate was 46%, including 15% CR/nCR. Median progression‐free survival was 11.4 months (95% confidence interval [CI]: 9.1‐12.7) from start of initial bortezomib treatment and 6.4 months (95% CI: 4.4‐7.2) from start of retreatment. Median overall survival from start of retreatment was 17.6 months (95% CI: 14.4‐23.5). Of the 96 patients retreated with bortezomib, 77% reported an AE. Peripheral neuropathy during bortezomib retreatment occurred in 49% of patients, including 10% grade 3/4. Conclusion: These data suggest that retreatment with bortezomib is a feasible option for patients with relapsed/refractory MM.